Highly Chemoselective Solvent-Free Synthesis of 1,3,5-Triaryl-1,5-diketones: Crystallographic Investigation and Intramolecular Weak Bifurcated H Bonds Involving Aliphatic C–H Group - Yin, Zhongyou; Xiong, Changkun; Guo, Jianxin; Hu, Xiaoyun; Shan, Zixing; Borovkov, Victor (Synlett, 2019)
Several 1,3,5-triaryl-1,5-diketones have been chemoselectively synthesized under solvent-free conditions. It was found that intramolecular weak bifurcated H-bonds interaction of aliphatic C–H group plays a decisive role in the structural arrangement of 3-(2,6-dichlorophenyl)-1,5-diphenylpentane-1,5-dione in a solid state resulting in significant impact on the corresponding bond lengths and dihedral angles.
Keywords: solvent-free reaction; intramolecular bifurcated weak bonds; X-ray crystallographic analysis; highly chemoselective synthesis; 1,5-diketones